2013
DOI: 10.1186/2193-1801-2-139
|View full text |Cite
|
Sign up to set email alerts
|

A review on the role of quinones in renal disorders

Abstract: Quinones are electron and proton carriers that play a primary role in the aerobic metabolism of virtually every cell in nature. Most physiological quinones are benzoquinones. They undergo highly regulated redox reactions in the mitochondria, Golgi apparatus, plasma membrane and endoplasmic reticulum. Important consequences of these electron transfer reactions are the production of and protection against reactive oxygen species (ROS). Quinones have been extensively studied for both their cytotoxic as well as ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 96 publications
0
22
0
1
Order By: Relevance
“…[1,2]. However, quinones generated in this reaction 49 are electron-deficient electrophilic compounds and may induce 50 damage in proteins as they react rapidly with nucleophilic sites 51 within proteins, such as cysteine thiols and lysine amines, to gen-52 erate post-translational modifications in the form of protein-phe-53 nol adducts [3,4]. The reaction between a quinone generated by the 54 oxidation of the catechol moiety of a phenol (1) and a free thiol 55 group in a protein is depicted in Scheme 1.…”
mentioning
confidence: 99%
“…[1,2]. However, quinones generated in this reaction 49 are electron-deficient electrophilic compounds and may induce 50 damage in proteins as they react rapidly with nucleophilic sites 51 within proteins, such as cysteine thiols and lysine amines, to gen-52 erate post-translational modifications in the form of protein-phe-53 nol adducts [3,4]. The reaction between a quinone generated by the 54 oxidation of the catechol moiety of a phenol (1) and a free thiol 55 group in a protein is depicted in Scheme 1.…”
mentioning
confidence: 99%
“…Quinones also enter the redox cycle with semiquinone radicals to form reactive oxygen compounds 14,15 . In addition, rhodamine can also penetrate into the cells and accumulate in the mitochondria to disrupt the respiratory chain 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The plasma membrane, endoplasmic reticulum, Golgi apparatus and the mitochondria are responsible for many of the exceedingly regulated redox reactions of aerobic metabolism and of equal importance are quinones which essentially are electron and proton carriers that play a primary role in the aerobic metabolism of practically every cell in nature. Although these redox reactions produce a significant amount of the energy the body needs to sustain life, these electron transfer reactions also consequently produce Reactive Oxygen Species (ROS) that play important roles in damage to the body at a molecular level (Madeo et al, 2013). Review of the literature, revealed evidence of significant correlations between production of ROS and inflammatory responses in an exponential relationship, as the production of ROS increases the greater the inflammatory response is.…”
Section: The Role Of the Mitochondrion In Trauma And Shock-a Non Infementioning
confidence: 99%
“…Review of the literature, revealed evidence of significant correlations between production of ROS and inflammatory responses in an exponential relationship, as the production of ROS increases the greater the inflammatory response is. The underlying mechanisms by which the inflammatory response and ROS production occur was also be discussed (Madeo et al, 2013;Saad et al, 2013).…”
Section: The Role Of the Mitochondrion In Trauma And Shock-a Non Infementioning
confidence: 99%